The Neotropical species of Atractodes (Hymenoptera, Ichneumonidae, Cryptinae), II: the A. pleuripunctatus species-group - Bordera, Santiago; Mazón, Marina; Sääksjärvi, Ilari E. (Zootaxa, 2016)
We describe three new species of parasitoid wasps of the genus Atractodes (Ichneumonidae: Cryptinae) from South America: A. colchaguensis sp. nov. from Chile, and A. pleuripunctatus sp. nov. and A. saragurensis sp. nov. from Ecuador. These species are all characterized by a densely and strongly punctate mesopleuron. The Atractodes pleuripunctatus species-group is defined to accommodate the new species. In addition, the second part of the key to species of the Neotropical Atractodes including this species-group is given.